Enhancement of plant growth and suppression of collar rot of sunflower caused by Sclerotium rolfsii through fluorescent Pseudomonas - and D.K. MAHESHWARI, SHIVANI BHATIA, R.C. DUBEY (Indian Phytopathology, 2005)
Ten isolates of fluorescent pseudomonads were isolated from rhizosphere of sunflower, potato, maize and groundnut. All the isolates produced fluorescent pigment in succinate broth and displayed siderophore production. Production of hydrocyanic acid (HCN)and indole acetic acid (IAA) by all the isolates was recorded besides phosphate solubilization. Out of the 10 strains, Pseudomonas PS I and PS II were found most potential. Bacterization of sunflower seeds with fluorescent Pseudomonas PS I and PS II resulted in increased seed germination, root length, shoot height, fresh and dry weight of roots and shoots, and yield of sunflower. Seed bacterization with strains of fluorescent Pseudomonas PS I and PS II reduced incidence of collar rot by 69.8% and 56.9%, respectively, in Sclerotium rolfsii-infested SOil, making the organism a potential biocontrol agent against collar rot of the sunflower.